Communication—Highly Efficient Electroenzymatic NADH Regeneration by an Electron-Relay Flavoenzyme. Issue 5 (1st January 2016) - Lee, Sumi; Choe, Hyunjun; Cho, Dae Haeng; Yoon, Sung Ho; Won, Keehoon; Kim, Yong Hwan
Abstract : Efficient cofactor regeneration is essential for the utilization of many oxidoreductases. Herein, the β-subunit of formate dehydrogenase 1 from Methylobacterium extorquens AM1 (MeFDH1-β) was employed as a novel electroactive biocatalyst for electroenzymatic NADH regeneration for the first time. MeFDH1-β showed much better properties in both catalytic activity (a turnover frequency of 3, 600 hr −1 ) and current efficiency (ca. 98%) than a conventional rhodium (III)-based chemical catalyst (M = [Cp * Rh(bpy)H2 O] 2+, Cp * = C5 Me5, bpy = 2, 2 ′ -bipyridine) and a traditional biocatalyst (diaphorase).